(untitled) (The Research of Medical Science Review, 2025)
Background: Community acquired pneumonia (CAP) is a major cause of illness and death world over. Determination of biomarkers that predict disease severity is important in getting the treatment on time and appropriate. D-dimer, a fibrin degradation product, is increased in cystic inflammation and coagulopathy which are common in severe infections. Its function as a prognostic indicator for CAP is being studied. Objectives: To determine the diagnostic accuracy of raised D-dimer level in determining the level of severity of community-acquired pneumonia, and to determine its association with clinical severity scores and patient outcomes. Study design: A cross- Sectional Validation Study. Place and duration of study. From 01 December 2023 to 31 May 2024, Medicine Department, Sandeman Provincial Hospital / Bolan Medical Complex Hospital Quetta Methods: On 207 patients diagnosed with CAP a cross Sectional Validation study was carried out. D-dimer levels were obtained on admission. The measure of clinical severity was done using the CURB-65 score. Data were analyzed with regard to the correlation between D-dimer and disease severity. Statistical calculation made included: mean, standard deviation, and p-values. The receiver operating characteristic (ROC) was applied for the analysis of diagnostic accuracy. Results: Two hundred and seven patients with community-acquired pneumonia were analyzed in the study. Average age was calculated at 58.6 ± 14.2 years. A high D-dimer level was identified in 148 patients (71.5%). Severely CAP infected (CURB-65 ≥3) patients had significantly elevated D-dimer levels than their counterparts (p < 0.001). The AUC on ROC curve analysis was 0.81 with good diagnostic accuracy for the prediction of severe CAP. High d-dimer levels (> than 1000 ng/mL) were strongly associated with a greater need for ICU admission and greater odds of 30-day mortality. Correlation between the levels of D-dimer and the CURB-65 scores was done and we found a strong positive correlation (r = 0.62, p < 0.001). Conclusion: Significantly increased D-dimer level is a strong predictor of community pneumonia severity. D-dimer has been demonstrated to have a good diagnostic performance in the prediction of disease severity and consequences to patients. Though not unique to CAP, this may act as an important adjunct biomarker for risk stratification and management decision. Complementation with clinical scoring systems such as CURB-65 increases its predictive value in clinical use.